Students' Perceptions of Individual Health at Different Stages of Life - Ermolaev B.V; Ermolaeva M.V; Lubovsky D.V (Moscow State University of Psychology and Education, 2018)
The paper analyses the problem of how health preservation is perceived by teenagers, adolescents and youths, demonstrating the need for research of students' perceptions of individual health and its preservation at different stages of life. An empirical study conducted with 522 students of the Moscow Polytechnic University (3 age groups, average age 17, 19 and 21 years) used a custom questionnaire aimed at examining their perceptions regarding the greatest value of the health factor at different stages of life from infancy to elderly age. The study revealed an unfortunate downward trend of individual health value with respect to the age when systematic health problems appear. Some gender differences in attitude towards individual health were discovered; for instance, women place a higher value on it for every stage of life and attach greater importance to it in early ontogeny. Men were found to overestimate the age associated with the onset of system health issues. The paper shows the possibilities for practical application of obtained data.